ChatGPT in academic assessments: upholding integrity - Adam Finkel-Gates (Journal of Learning Development in Higher Education)
This study examines the impact of AI, particularly ChatGPT, on academic integrity and assessment practices in higher education. As AI integration grows, concerns about its potential to undermine academic rigour and increase inequalities have surfaced. Through interviews with students and a lecturer, the research explores the benefits and challenges of using ChatGPT in academic work. The innovative approach of having students use ChatGPT to write assignments highlights both efficiency gains and the need for responsible use. Findings reveal the importance of using AI-generated content as a supplement rather than a replacement for traditional learning, with concerns about its potential misuse. The study advocates for updated integrity policies and clear guidelines to ensure AI enhances, rather than compromises, education. Emphasising ethical AI use and process-oriented assessments, the study offers strategies to promote fairness, integrity, and critical thinking in the digital age.